Discussion of Evolution Between Neo-Lamarckism and Neo-Darwinism in the Czech Lands, 1900–1915 - Hermann, Tomáš; Šimůnek, Michal (Teorie vědy / Theory of Science, 2010)
The present study focuses on the impact which the vast, fundamental changes in biology of the late 19th and early 20th century had in the Czech Lands. Until the WWI, there existed several distinct and often mutually contradictory theories of evolution of organisms. In the Czech Lands, this multitude of theoretical explanations was complemented by a multi-layered cultural and scientific environment, where Czech and German biology influenced each other and met at various autonomous institutions. One should also keep in mind the differences between Prague and Brno, each a local centre with its scientific traditions and independent links to both Vienna and other European universities. The main subject of this paper are the theoretical biologists who had long-term impact on Czech biological thought or influenced it directly by working here. In about 1900-1915, we witness the first clear and recognised peak in the Czech reception of evolutionism.